Rickettsia sp. em roedores e marsupiais silvestres do Rio Grande do Norte, Brasil - Paiva, Kaliane Alessandra Rodrigues de (Universidade Federal Rural do Semi-Árido, 2016)
Rickettsia are pathogens with zoonotic potential transmitted by wild and domestic animals, where the occurrence of infections by Rickettsia spp. It happens among populations of wild rodents and marsupials, which has a significant share in the maintenance cycle of these microorganisms in the wild environment. Thus, this study aimed to record the occurrence of Rickettsia sp. in wild rodents and marsupials in the Rio Grande do Norte semi-arid. The work consisted in a field research with wild rodents and marsupials, with data expressed in simple frequency and percentage using IBM SPSS (Armonk, NY: IBM Corp.), version 22.0. Were captured in Sherman and Tomahawk traps, 02 Thrichomys, 03 Wiedomys, 30 Gracilinanus agilis and 06 Monodelphis domestica, which were collected by venipuncture of julgular vein, 36 blood samples of marsupials and 05 of rodents. These were collected 64 Amblyomma auricularium, 07 Amblyomma parvum and 12 Amblyomma sp. Were obtained by centrifugation 36 samples of sera marsupials and 05 rodents and analyzed using Immunofluorescence Assay (IFA). All copies of A. auricularium, Amblyomma sp. and A. parvum were macerated and submitted to DNA extraction and amplification by Polymerase Chain Reaction (PCR) directed to a fragment of gltA and ompA rickettsial genes. Of serum samples obtained from wild rodents and marsupials blood and tested in IFA showed seropositivity for Rickettsia amblyommii, 6.7% G. agilis, 83.3% M. domestica and 50% Thrichomys. Eight samples of A. auricularium were positive for genes in R. amblyommii fragment analysis gltA (350 bp) and ompA (587 bp) with 100% similarity to Candidatus R. amblyommii Bahia and AaPE strain, corresponding to a low circulation agent from the vectors and high among the population of M. domestica. This research records for the first time the occurrence of R. amblyommii in marsupial species G. agilis and M. domestica belonging to Didelphidae family and Echimyidae family rodents Thrichomys genre, in the semiarid region of Rio Grande do Norte, Brazil
Rickettsia sp. in wild rodents and marsupials of Rio Grande do Norte, Brazil
Keywords: Animais silvestres; Marsupial; Roedor; Rickettsia; Soropositividade; Wild animals; Marsupials; Rodents; Rickettsia; Seropositivity; CIENCIAS AGRARIAS::MEDICINA VETERINARIA